(untitled) (Revista Brasileira Multidisciplinar, 2010)
This research was developed in the city of New Friburgo, more precisely in the seventh section – Lumiar – Rio Bonito. The inexistence in the region of educational actions aimed at understanding, reflecting and offering information to the population on the main environmental subjects has leaded to an environmental diagnosis, to identify the local community problems and, later, to develop educational environmental activities at municipal school Nossa Senhora de Nazareth. To attain this aim, the selected educational strategy was story telling. The research instrument was a questionnaire addressed to the families and to the teachers. Based on the principal detected problems, the ones related to environmental issues were selected, such as: river pollution; the release of solid residues in not appropriate places and the armed hunting. Those subjects were discussed with the local school students through story telling. Other playful educational activities were also developed. Finally, it could be observed that, not only the stories, but also the complementary activities, have helped the students in the environmental education work, considering that besides showing interest in the subject, they participated intensely, reflected, changed and built knowledge.